Stratified primary care versus non-stratified care for musculoskeletal pain : qualitative findings from the STarT MSK feasibility and pilot cluster randomized controlled trial - Saunders, Benjamin (2021)
Background: Stratified care involves subgrouping patients based on key characteristics, e.g. prognostic risk, and matching these subgroups to appropriate early treatment options. The STarT MSK feasibility and pilot cluster randomised controlled trial (RCT) examined the feasibility of a future main trial and of delivering prognostic stratified primary care for patients with musculoskeletal pain. The pilot RCT was conducted in 8 UK general practices (4 stratified care; 4 usual care) with 524 patients. GPs in stratified care practices were asked to use i) the Keele STarT MSK development tool for risk-stratification and ii) matched treatment options for patients at low-, medium- and high-risk of persistent pain. This paper reports on a nested qualitative study exploring the feasibility of delivering stratified care ahead of the main trial. Methods: ‘Stimulated-recall’ interviews were conducted with patients and GPs in the stratified care arm (n = 10 patients; 10 GPs), prompted by consultation recordings. Data were analysed thematically and mapped onto the COM-B behaviour change model; exploring the Capability, Opportunity and Motivation GPs and patients had to engage with stratified care. Results: Patients reported positive views that stratified care enabled a more ‘structured’ consultation, and felt tool items were useful in making GPs aware of patients’ worries and concerns. However, the closed nature of the tool’s items was seen as a barrier to opening up discussion. GPs identified difficulties integrating the tool within consultations (Opportunity), but found this easier as it became more familiar. Whilst both groups felt the tool had added value, they identified ‘cumbersome’ items which made it more difficult to use (Capability). Most GPs reported that the matched treatment options aided their clinical decision-making (Motivation), but identified some options that were not available to them (e.g. pain management clinics), and other options that were not included in the matched treatments but which were felt appropriate for some patients (e.g. consider imaging). Conclusion: This nested qualitative study, using the COM-B model, identified amendments required for the main trial including changes to the Keele STarT MSK tool and matched treatment options, targeting the COM-B model constructs, and these have been implemented in the current main trial.